Irreversible additive, positive electrode material containing the irreversible additive, and lithium secondary battery containing the positive electrode material
By using irreversible additives with trigonometric crystal structure and LISICON-based coatings in lithium secondary batteries, the problem of irreversible capacity increases in lithium secondary batteries is solved, and higher energy density and structural stability are achieved sex.
Patent Information
- Application Number
- CN202080076025.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-11-11
- Filing Date
- 2020-11-11
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2040-11-11
AI Technical Summary
After initial charging, the existing lithium secondary batteries increase irreversible capacity due to prelithiation of the negative electrode active material, thereby reducing the energy density.
An irreversible additive is used, which consists of lithium nickel oxide having a trigonometric crystal structure and LISICON-based compounds in the surface coating. Through the composition and structural design of these compounds, structural deterioration of lithium ions and gas generation are inhibited.
It effectively reduces the structural deterioration and irreversible capacity of lithium secondary batteries during charging/discharging, and improves the energy density and structural stability of the battery.
Smart Images

Figure CN114631207B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to an irreversible additive, a positive electrode material for a lithium secondary battery containing the irreversible additive, and a lithium secondary battery containing the positive electrode material. Background Art
[0002] As the technology development and demand for mobile devices increase, the demand for secondary batteries as energy sources has rapidly increased. Among such secondary batteries, lithium secondary batteries with high energy density and operating potential, long cycle life, and low self-discharge rate have been commercialized and widely used.
[0003] Lithium secondary batteries are generally composed of a positive electrode containing a positive electrode active material, a negative electrode containing a negative electrode active material, a separator and an electrolyte. They are a type of secondary battery that is charged and discharged by the insertion and extraction of lithium ions. Lithium secondary batteries have the advantages of high energy density, high electromotive force and high capacity, and are therefore used in various fields.
[0004] Various methods have been studied to achieve lithium secondary batteries with higher capacity. Specifically, a method has been attempted in which one or more materials such as LCO, LNMCO, LMO, etc. are used as positive electrode active materials contained in the positive electrode for lithium secondary batteries to achieve high-capacity lithium secondary batteries. However, in order to increase the capacity of lithium secondary batteries, it is necessary not only to increase the capacity of the positive electrode but also to increase the capacity of the negative electrode. To this end, a method has also been attempted in which a silicon-based negative electrode active material with high capacity is used as the negative electrode. However, in the case of a battery using such a silicon-based negative electrode active material, the electrolyte decomposes during the initial charge, resulting in the formation of a solid electrolyte interface (SEI) layer on the surface of the negative electrode active material, so that irreversible capacity is generated accordingly. Due to the generation of irreversible capacity, the energy density is reduced, so that there is a problem that the secondary battery is not fully utilized to its theoretical capacity.
[0005] Therefore, Li2NiO2 is usually added as a sacrificial positive electrode material to solve the problem of irreversible capacity caused by pre-lithiation of the negative electrode.
[0006] However, although Li2NiO2, which is generally used as a sacrificial positive electrode material, has an orthorhombic structure and has an Immm space group, it undergoes structural changes in three stages within a usable voltage range after initial charge, causing side reactions such as impurity generation, gas generation, etc. Specifically, after initial charge, Li2NiO2 maintains an orthorhombic structure and an Immm space group at 3.0V to 3.5V, its structure transforms into a trigonal structure at 3.5V to 4.0V, and transforms into a monoclinic structure at 4.0V to 4.25V, causing problems due to its structural changes.
[0007] Therefore, it is necessary to develop an additive that enables lithium ions to fully appear during initial charging and does not cause impurity generation or gas generation due to structural changes within a usable voltage range in subsequent charging and discharging. Summary of the invention
[0008] Technical issues
[0009] In order to solve the above problems, a first aspect of the present invention provides an irreversible additive capable of minimizing structural changes in a usable voltage range during charge and discharge and suppressing gas generation and side reactions on the surface by being present as a coating on the surface.
[0010] A second aspect of the present invention provides a positive electrode material for a secondary battery comprising the irreversible additive.
[0011] A third aspect of the present invention provides a lithium secondary battery comprising the positive electrode material.
[0012] Technical Solution
[0013] According to one aspect of the present invention, an irreversible additive is provided, comprising an oxide having a trigonal crystal structure and represented by the following Formula 1, and a coating layer located on the surface of the oxide represented by Formula 1 and comprising a compound represented by the following Formula 2.
[0014] [Formula 1]
[0015] Li 2+a Ni 1-b M1 b O 2+c
[0016] In the above formula 1, 0≤a≤0.2, 0≤b≤0.5, and 0≤c≤0.2, and M1 is one or more selected from the group consisting of Cu, Mg, Pt, Al, Co, P, and B.
[0017] [Formula 2]
[0018] Li 5+c FeO 4-d A d
[0019] In the above formula 2, 0≤c≤0.2 and 0≤d≤0.5, preferably 0≤c≤0.1 and 0≤d≤0.2, and A is one or more selected from the group consisting of F, Cl, Br, I, At and S.
[0020] According to another aspect of the present invention, there are provided a positive electrode material including the irreversible additive and a positive electrode active material, and a lithium secondary battery including the positive electrode material.
[0021] Beneficial Effects
[0022] The irreversible additive according to the present invention includes lithium nickel oxide having a trigonal crystal structure, whereby the crystal structure change of the irreversible additive within the driving voltage range of the secondary battery is minimized, thereby suppressing structural degradation of the irreversible additive during charge / discharge.
[0023] In addition, the irreversible additive according to the present invention has a coating formed on the surface of the nickel lithium oxide, the coating having an orthorhombic structure and containing a compound as LISICON, thereby stabilizing the structure of the orthorhombic lithium nickel oxide, increasing lithium ion mobility, and minimizing the contact between the electrolyte and the lithium nickel oxide.
[0024] As a result, the irreversible additive according to the present invention has excellent structural stability compared to a typical irreversible additive including orthorhombic lithium nickel oxide, and can also significantly reduce gas generation and lithium by-product generation due to a side reaction with an electrolyte. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 A schematic diagram showing a lithium nickel oxide having a trigonal crystal structure belonging to a space group P3-m1;
[0026] Figure 2 A schematic diagram showing a LISICON structure compound having an orthorhombic crystal structure belonging to the space group Pbca;
[0027] Figure 3 The figure shows the X-ray diffraction (XRD) pattern of the Li2NiO2 powder prepared in Example 1;
[0028] Figure 4 : shows the X-ray diffraction (XRD) pattern of the Li5FeO4 powder prepared in Example 1; and
[0029] Figure 5 The figure shows the X-ray diffraction (XRD) pattern of Li2NiO2 powder prepared as an irreversible additive in Comparative Example 1. DETAILED DESCRIPTION
[0030] Hereinafter, the present invention will be described in more detail.
[0031] It should be understood that the words or terms used in the specification and claims of the present invention should not be interpreted as limited to the meanings defined in commonly used dictionaries. It should be further understood that based on the principle that the inventor can appropriately define the meaning of words or terms to best interpret the present invention, the words or terms should be interpreted as having a meaning consistent with their meaning in the context of the relevant fields and technical concepts of the present invention.
[0032] Irreversible additives
[0033] The present inventors have discovered that when a lithium nickel oxide having a specific crystal structure, specifically a trigonal crystal structure, is used as an irreversible additive, structural changes of the irreversible additive during charging and discharging can be suppressed, and when a lithium superion conductor (LISICON)-based compound is coated on its surface, the structural stability of the trigonal lithium nickel oxide can be increased and the lithium ion mobility during initial charging and discharging can be improved, thereby effectively compensating for the irreversible capacity of the negative electrode, and the present invention has been completed.
[0034] Specifically, the irreversible additive according to the present invention includes a lithium nickel oxide having a trigonal crystal structure and represented by the following Formula 1, and a coating layer located on the surface of the lithium nickel oxide represented by Formula 1 and including a compound represented by the following Formula 2.
[0035] [Formula 1]
[0036] Li 2+a Ni 1-b M1 b O 2+c
[0037] In the above formula 1, 0≤a≤0.2, 0≤b≤0.5, and 0≤c≤0.2, and M1 is one or more selected from the group consisting of Cu, Mg, Pt, Al, Co, P, and B.
[0038] [Formula 2]
[0039] Li 5+c FeO 4-d A d
[0040] In the above formula 2, 0≤c≤0.2 and 0≤d≤0.5, preferably 0≤c≤0.1 and 0≤d≤0.2, and A is one or more selected from the group consisting of F, Cl, Br, I, At and S.
[0041] Figure 1 A schematic diagram showing lithium nickel oxide having a trigonal crystal structure belonging to a space group of P3-m1.
[0042] The trigonal crystal structure means that the three axes in the crystal have the same length, and the angles between the axes are also the same, but different from 90°. Specifically, the trigonal crystal structure means that a=b=c and ∠α=∠β=∠γ≠90°. The oxide having the crystal structure as described above can reversibly embed and deintercalate lithium ions, and because the crystal structure has a two-dimensional layered structure, ion diffusion can occur quickly.
[0043] Specifically, the lithium nickel oxide may be represented by Formula 1 below.
[0044] [Formula 1]
[0045] Li 2+a Ni 1-b M1 b O 2+c
[0046] In the above formula 1, 0≤a≤0.2, 0≤b≤0.5, and 0≤c≤0.2, and M1 is one or more selected from the group consisting of Cu, Mg, Pt, Al, Co, P, and B.
[0047] The lithium nickel oxide represented by the above formula 1 may contain lithium and nickel in a molar ratio of 1.5: 1 to 2: 1, preferably 1.8: 1 to 2: 1, and most preferably 2: 1. Preferably, the oxide represented by the above formula 1 may be Li2NiO2. When the molar ratio of lithium and nickel satisfies the above range, the formation of a trigonal crystal structure can be stably achieved.
[0048] As is well known, lithium nickel oxide, which is generally used as an irreversible additive, forms an orthorhombic crystal structure. However, when preparing lithium nickel oxide, if the lithium nickel oxide is synthesized by mixing with a lithium:nickel (Li / Ni) molar ratio of 2 or more, and / or by reacting LiNiO2 and a lithium raw material in an inert atmosphere in a wet process, a lithium nickel oxide having a trigonal crystal structure can be prepared.
[0049] On the other hand, the lithium nickel oxide with an orthorhombic structure can undergo at least three stages of structural changes within the usable voltage range of the secondary battery. Specifically, the lithium nickel oxide maintains an orthorhombic structure when it is in the voltage range of 3.0V to 3.5V, and as the voltage increases, it is transformed into a trigonal structure due to lithium ion deintercalation in the voltage range of 3.5V to 4.0V, and then, in the voltage range of 4.0V to 4.25V, it is transformed into a monoclinic structure as lithium is further deintercalated. When at least three stages of structural changes occur as described above, the structural stability of the lithium nickel oxide deteriorates due to structural transformation, which may cause problems such as lithium byproduct generation and gas generation.
[0050] In contrast, in the case of a lithium nickel oxide having a trigonal structure, the oxide does not participate in the reaction at a voltage lower than 3.5 V, maintains a trigonal structure in a voltage range of 3.5 V to 4.0 V, and as the voltage increases, changes to a monoclinic structure due to lithium ion deintercalation in a voltage range of 4.0 V to 4.25 V, which belongs to the C2 / m space group. Therefore, compared with the case of using a lithium nickel oxide having an orthorhombic structure, when a lithium nickel oxide having a trigonal structure is used as in the present invention, the crystal structure changes less during the charge / discharge process, so that the deterioration of the structural stability due to the crystal structure change can be minimized.
[0051] In addition, the irreversible additive of the present invention includes a coating layer having a compound represented by Formula 2 on the surface of the lithium nickel oxide of Formula 1 having a trigonal crystal structure.
[0052] [Formula 2]
[0053] Li 5+c FeO 4-d A d
[0054] In Formula 2 above, 0≤c≤0.2 and 0≤d≤0.5, preferably 0≤c≤0.1 and 0≤d≤0.2, and A includes one or more selected from the group consisting of F, Cl, Br, I, At and S. Most preferably, the compound represented by Formula 2 above may be Li5FeO4.
[0055] The compound represented by the above formula 2 is a LISICON-based compound having high lithium ion conductivity, and therefore, when the surface of the lithium nickel oxide represented by formula 1 is coated with the compound of the above formula 2, the lithium ion mobility increases to more effectively achieve compensation for the irreversible capacity of the negative electrode during initial charging (activation process).
[0056] In addition, when the surface of the lithium nickel oxide is coated with the compound of Formula 2, the surface structure is stabilized by the compound of Formula 2, so that the rapid structural degradation of the irreversible additive can be prevented, and the lithium nickel oxide and the electrolyte are prevented from directly contacting each other, thereby effectively suppressing the gas generation and lithium by-product generation caused by the side reaction with the electrolyte.
[0057] On the other hand, the compound of Formula 2 above has an orthorhombic crystal structure, and may exhibit a Pbca space group.
[0058] Figure 2 A schematic diagram of a compound having an orthorhombic crystal structure belonging to the space group Pbca is shown.
[0059] The orthorhombic crystal structure belonging to the space group Pbca refers to a crystal structure having three orthogonal crystal axes, wherein the axes have different lengths from each other and have a secondary symmetry axis parallel to the main axis. Specifically, the orthorhombic crystal structure means a≠b≠c and ∠α=∠β=∠γ=90°, and the lattice parameters of the present invention are represented by and Best and Best choice and
[0060] On the other hand, the irreversible additive according to the present invention may include a compound represented by the above formula 2 in an amount of 1 to 10 parts by weight, preferably 1 to 5 parts by weight, based on 100 parts by weight of the total weight of the lithium nickel oxide represented by the above formula 1. When the content of the compound of formula 2 satisfies the above range, the generation of surface side reactions can be suppressed while minimizing the degradation of the irreversible capacity.
[0061] On the other hand, the coating layer may be uniformly distributed on the entire surface of the lithium nickel oxide represented by the above Formula 1, or may be distributed in the form of partially aggregated islands.
[0062] Cathode Materials
[0063] In addition, the present invention provides a positive electrode material for a lithium secondary battery, the positive electrode material comprising the above irreversible additive and a positive electrode active material.
[0064] The irreversible additive has been described. Therefore, the positive electrode active material will be described below.
[0065] Any material commonly used as a positive electrode active material can be used as the positive electrode active material without particular limitation. Specific examples thereof may be layered compounds such as lithium cobalt oxide (LiCoO2) and lithium nickel oxide (LiNiO2), or compounds replaced by one or more transition metals; 1+y1 Mn 2-y1 Lithium manganese oxide represented by LiMnO4 (0≤y1≤0.33), LiMnO3, LiMn2O3 or LiMnO2; lithium copper oxide (Li2CuO2); vanadium oxide, such as LiV3O8, LiFe3O4, V2O5 and Cu2V2O7; LiNi 1-y2 M y2 Ni-site lithium nickel oxide represented by O2 (wherein M is one or more selected from the group consisting of Co, Mn, Al, Cu, Fe, Mg, B and Ga, and 0.01≤y2≤0.3); 2-y3 M y3O2 (where M is one or more selected from the group consisting of Co, Ni, Fe, Cr, Zn, and Ta, and 0.01 ≤ y3 ≤ 0.1) or a lithium manganese composite oxide represented by the formula Li2Mn3MO8 (where M is one or more selected from the group consisting of Fe, Co, Ni, Cu, or Zn); LiMn2O4, wherein a part of Li in the formula is replaced by an alkaline earth metal ion, etc., but the positive electrode active material is not limited thereto. The positive electrode may be Li metal.
[0066] Preferably, the positive electrode active material may be a lithium nickel cobalt-based oxide represented by the following formula 3.
[0067] [Formula 3]
[0068] Li 1+f Ni x Co y M3 z M4 w O2
[0069] In the above formula 3, M3 may be one or more of Mn and Al, and M4 may be one or more selected from the group consisting of Al, Mg, Ti, W, Zr, V, Fe, Y, and Mo.
[0070] 1 + f is the atomic ratio of lithium in the lithium nickel cobalt-based oxide, where f may satisfy 0 ≤ f ≤ 0.2, or 0 ≤ f ≤ 0.1.
[0071] x is the atomic ratio of nickel among the transition metals in the lithium nickel cobalt-based oxide, where x may satisfy 0 < x < 1, 0.3 ≤ x < 1, 0.6 ≤ x < 1, 0.8 ≤ x < 1, or 0.9 ≤ x < 1.
[0072] y is the atomic ratio of cobalt among the transition metals in the lithium nickel cobalt-based oxide, where y may satisfy 0 < y < 1, 0 < y < 0.7, 0 < y < 0.4, 0 < y < 0.2, or 0 < y < 0.1.
[0073] z is the atomic ratio of M3 among the transition metals in the lithium nickel cobalt-based oxide, where z may satisfy 0 < z < 1, 0 < z < 0.7, 0 < z < 0.4, 0 < z < 0.2, or 0 < z < 0.1.
[0074] w is the atomic ratio of M4 among the transition metals in the lithium nickel cobalt-based oxide, where w may satisfy 0 ≤ w ≤ 0.1 or 0 ≤ w ≤ 0.05.
[0075] More preferably, the positive electrode active material may be a lithium nickel cobalt manganese aluminum oxide represented by the following formula 4.
[0076] [Formula 4]
[0077] Li 1+f1Ni x1 Co y1 Mn z1 Al z2 M4 w1 O2
[0078] In Formula 4 above, M4 can be one or more selected from the group consisting of Mg, Ti, W, Zr, V, Fe, Y, and Mo.
[0079] 1 + f1 is the atomic ratio of lithium in the lithium nickel cobalt manganese aluminum oxide, where f can satisfy 0 ≤ f1 ≤ 0.2, or 0 ≤ f1 ≤ 0.1.
[0080] x1 is the atomic ratio of nickel among the transition metals in the lithium nickel cobalt manganese aluminum oxide, where x1 can satisfy 0.8 ≤ x1 < 1, 0.85 ≤ x1 < 1, or 0.9 ≤ x1 < 1.
[0081] y1 is the atomic ratio of cobalt among the transition metals in the lithium nickel cobalt manganese aluminum oxide, where y1 can satisfy 0 < y1 < 0.2, 0 < y1 < 0.1, or 0 < y1 ≤ 0.05.
[0082] z1 is the atomic ratio of Mn among the transition metals in the lithium nickel cobalt manganese aluminum oxide, where z1 can satisfy 0 < z1 < 0.2, 0 < z1 < 0.1, or 0 < z1 ≤ 0.05.
[0083] z2 is the atomic ratio of Al among the transition metals in the lithium nickel cobalt manganese aluminum oxide, where z2 can satisfy 0 < z2 < 0.2, 0 < z2 < 0.1, or 0 < z2 ≤ 0.05.
[0084] w1 is the atomic ratio of M4 among the transition metals in the lithium nickel cobalt manganese aluminum oxide, where w1 can satisfy 0 ≤ w1 ≤ 0.1, 0 ≤ w1 ≤ 0.05, or 0 ≤ w1 ≤ 0.02.
[0085] On the other hand, the insertion and extraction of lithium ions during charging and discharging may change the crystal structure of the positive electrode active material. For example, the positive electrode active material of Formula 3 or Formula 4 above has a hexagonal crystal structure before charging. However, after charging and discharging, due to the insertion and extraction of lithium ions, its crystal structure changes to a monoclinic structure. When using the positive electrode active material of Formula 3 or Formula 4 that changes to a monoclinic structure during charging and discharging, the crystal structures of the positive electrode active material and the irreversible additive become monoclinic structures, so that the lithium ion diffusion rate is maintained constant during the insertion and extraction of lithium ions, and thus there may be an effect of more easily overcoming the irreversible capacity.
[0086] The content of the positive electrode active material and the irreversible additive contained in the positive electrode material is not particularly limited. Preferably, the content of the irreversible additive may be a content that can suppress the irreversible capacity of the negative electrode without reducing the energy density of the secondary battery. Preferably, the content of the irreversible additive may be 5 to 20 parts by weight based on 100 parts by weight of the positive electrode active material.
[0087] For example, when the positive electrode active material represented by Formula 3 or Formula 4 as described above is used as the positive electrode active material and the silicon-based negative electrode is used as the negative electrode, the content of the irreversible additive contained in the positive electrode material may be 5 to 20 parts by weight, preferably 10 to 15 parts by weight, based on 100 parts by weight of the positive electrode active material. When the positive electrode material containing the positive electrode active material and the irreversible additive within the above range is applied to a battery, the problem of irreversible capacity can be solved without reducing the energy density of the secondary battery.
[0088] positive electrode
[0089] In addition, the present invention provides a positive electrode for a lithium secondary battery, the positive electrode comprising the positive electrode material produced by the above method.
[0090] Specifically, the positive electrode includes a positive electrode current collector and a positive electrode material layer formed on at least one surface of the positive electrode current collector and including the positive electrode material.
[0091] The positive electrode current collector is not particularly limited as long as it has conductivity and does not cause chemical changes in the battery. For example, stainless steel, aluminum, nickel, titanium, fired carbon, or aluminum or stainless steel surface-treated with one of carbon, nickel, titanium, silver, etc. can be used. In addition, the positive electrode current collector may generally have a thickness of 3 μm to 500 μm, and fine concavoconvexities may be formed on the surface of the positive electrode current collector to improve the adhesion of the positive electrode material. For example, various forms of positive electrode current collectors such as films, sheets, foils, nets, porous bodies, foams, and non-woven fabrics may be used.
[0092] The positive electrode material layer may include a conductive material and a binder in addition to the positive electrode material.
[0093] At this time, the content of the positive electrode material may be 80-99 wt %, more specifically 85-98 wt %, based on the total weight of the positive electrode material layer. When included in the above content range, excellent capacity properties may be exhibited.
[0094] At this time, the conductive material is used to give the electrode conductivity, and any conductive material can be used without particular limitation as long as it has electronic conductivity and does not cause chemical changes in the battery to be constructed. Specific examples thereof may include: graphite, such as natural graphite or artificial graphite, etc.; carbon-based materials, such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black and carbon fiber; metal powders or metal fibers of copper, nickel, aluminum and silver, etc.; conductive whiskers, such as zinc oxide whiskers and potassium titanate whiskers; conductive metal oxides, such as titanium oxide; or conductive polymers, such as polyphenylene derivatives, and any one thereof or a mixture of two or more thereof can be used. The content of the conductive material may be 1 to 30% by weight based on the total weight of the positive electrode material layer.
[0095] The binder is used to improve the bonding between the positive electrode material particles and the adhesion between the positive electrode material and the collector. Its specific examples may include polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-to-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene monomer (EPDM), sulfonated EPDM, styrene-butadiene rubber (SBR), fluororubber or its various copolymers, and any one thereof or a mixture of two or more thereof can be used. Based on the gross weight of the positive electrode material layer, the content of the binder may be 1 to 30 weight %.
[0096] The positive electrode can be manufactured according to a typical method for manufacturing a positive electrode, except that the above-mentioned positive electrode material is used. Specifically, the positive electrode can be manufactured by applying a positive electrode material layer forming composition on a positive electrode current collector, followed by drying and rolling, wherein the composition is prepared by dissolving or dispersing the above-mentioned positive electrode material and a selective binder and a conductive material in a solvent. At this time, the types and contents of the positive electrode material, binder and conductive material are as described above.
[0097] The solvent may be a commonly used solvent in the art, and may be dimethyl sulfoxide (DMSO), isopropanol, N-methylpyrrolidone (NMP), acetone, water, etc. Any one thereof or a mixture of two or more thereof may be used. If the thickness of the slurry applied and the yield of the preparation are taken into consideration, the solvent may dissolve and disperse the cathode material, the binder, and the conductive material, and then, during the application to manufacture the cathode, the solvent may have a viscosity that exhibits excellent thickness uniformity, and the amount of the solvent used is sufficient.
[0098] In addition, in another method, the positive electrode may be manufactured by casting the positive electrode material layer-forming composition on a separate support and then laminating a film obtained by peeling off the support on a positive electrode current collector.
[0099] Lithium secondary battery
[0100] In addition, the present invention can manufacture an electrochemical device including the positive electrode. The electrochemical device can be specifically a battery, a capacitor, etc., and more specifically, a lithium secondary battery.
[0101] Specifically, the lithium secondary battery comprises a positive electrode, a negative electrode positioned facing the positive electrode, a separator between the positive electrode and the negative electrode, and an electrolyte. The positive electrode is the same as described above, and therefore, a detailed description thereof will be omitted. Hereinafter, only the remaining components will be described in detail.
[0102] In addition, the lithium secondary battery may selectively further include a battery case for accommodating an electrode assembly consisting of the positive electrode, the negative electrode, and the separator, and a sealing member for sealing the battery case.
[0103] In the lithium secondary battery, the negative electrode includes a negative electrode current collector and a negative electrode active material layer located on the negative electrode current collector.
[0104] The negative electrode current collector is not particularly limited as long as it has high conductivity and does not cause chemical changes in the battery. For example, copper, stainless steel, aluminum, nickel, titanium, fired carbon, copper or stainless steel surface-treated with one of carbon, nickel, titanium, silver, etc., aluminum-cadmium alloy, etc. can be used. In addition, the negative electrode current collector may generally have a thickness of 3 μm to 500 μm, and as in the case of the positive electrode current collector, fine concave-convex shapes may be formed on the surface of the negative electrode current collector to improve the adhesion of the negative electrode active material. For example, various forms of negative electrode current collectors may be used, such as films, sheets, foils, nets, porous bodies, foams, and non-woven fabrics.
[0105] The negative electrode active material layer contains not only the negative electrode active material but also selectively contains a binder and a conductive material.
[0106] As the negative electrode active material, a single substance or compound capable of reversibly inserting and deinserting lithium can be used. Specific examples thereof may include carbonaceous materials such as artificial graphite, natural graphite, graphitized carbon fiber, and amorphous carbon; metals or metal compounds that can be alloyed with lithium, such as Si, Al, Sn, Pb, Zn, Bi, In, Mg, Ga, Cd, Si alloys, Sn alloys, or Al alloys; metal oxides that can be doped and dedoped with lithium, such as SiO β(0<β<2), SnO2, vanadium oxide and lithium vanadium oxide; or a composite comprising the metal or metal compound and the carbonaceous material, such as a Si-C composite or a Sn-C composite, and any one thereof or a mixture of two or more thereof can be used. Metal lithium film can also be used as the negative electrode active material. In addition, low-crystalline carbon, high-crystalline carbon, etc. can be used as carbon materials. Representative examples of the low-crystalline carbon may include soft carbon and hard carbon, and representative examples of the high-crystalline carbon may include irregular, plate-like, flaky, spherical or fibrous natural graphite or artificial graphite, floating graphite, pyrolytic carbon, mesophase pitch-based carbon fibers, mesophase carbon microspheres, mesophase pitch, and high-temperature sintered carbon such as coke derived from petroleum or coal tar pitch. In order to achieve high capacity of secondary batteries, it is preferred to use a negative electrode containing a silicon-based negative electrode active material as the negative electrode.
[0107] For example, when the negative electrode includes a silicon-based negative electrode active material, a high-capacity secondary battery can be achieved. However, due to the high irreversible capacity of the silicon-based negative electrode active material, there is a disadvantage that the energy density of the secondary battery is reduced.
[0108] Therefore, in the present invention, the above-mentioned irreversible additive is included in the positive electrode for a secondary battery, whereby lithium ions contained in the irreversible additive move to the negative electrode during initial charging, resulting in pre-lithiation of the negative electrode, thereby reducing the irreversible capacity of the negative electrode.
[0109] The negative electrode active material may be included in an amount of 80 parts by weight to 99 parts by weight based on 100 parts by weight of the total weight of the negative electrode active material layer.
[0110] The binder is a component for helping the bonding between the conductive material, the active material and the current collector, and is generally added in an amount of 0.1 to 10 parts by weight based on 100 parts by weight of the total weight of the negative electrode active material layer. Examples of the binder may include polyvinylidene fluoride (PVDF), polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene monomer (EPDM), sulfonated EPDM, styrene-butadiene rubber, nitrile rubber, fluororubber, various copolymers thereof, and the like.
[0111] The conductive material is a component for further improving the conductivity of the negative electrode active material, and the addition amount may be 10 parts by weight or less, specifically 5 parts by weight or less, based on 100 parts by weight of the total weight of the negative electrode active material layer. The conductive material is not particularly limited as long as it has conductivity and does not cause chemical changes in the battery. For example, graphite such as natural graphite or artificial graphite; carbon black such as acetylene black, ketjen black, channel black, furnace black, lamp black, and thermal black; conductive fibers such as carbon fibers and metal fibers; fluorocarbon powders; metal powders such as aluminum powder and nickel powder; conductive whiskers of zinc oxide and potassium titanate, etc.; conductive metal oxides such as titanium oxide; or conductive materials such as polyphenylene derivatives, etc. may be used.
[0112] For example, the negative electrode active material layer may be prepared by applying a negative electrode mixture material on a negative electrode current collector and then drying it, wherein the negative electrode mixture material is prepared by dissolving or dispersing a negative electrode active material and a selective binder and a conductive material in a solvent. Alternatively, the negative electrode active material layer may be prepared by casting the negative electrode mixture material on a separate support and then laminating the film peeled off from the support on a negative electrode current collector.
[0113] The negative electrode active material layer can be prepared, for example, by applying a negative electrode mixture material on a negative electrode current collector and then drying it, wherein the negative electrode mixture material is prepared by dissolving or dispersing a negative electrode active material and an optional binder and a conductive material in a solvent. Alternatively, the negative electrode active material layer can be prepared by casting the negative electrode mixture material on a separate support and then laminating the film peeled off from the support on the negative electrode current collector.
[0114] On the other hand, in the lithium secondary battery, the separator separates the negative electrode and the positive electrode and provides a mobile path for lithium ions. Any separator can be used without particular limitation, as long as it is generally used as a separator in a lithium secondary battery. In particular, a separator with high moisture capacity for electrolyte and low movement resistance to electrolyte ions is preferred. Specifically, a porous polymer film can be used, for example, a porous polymer film made of a polyolefin-based polymer such as ethylene homopolymer, propylene homopolymer, ethylene / butene copolymer, ethylene / hexene copolymer, and ethylene / methacrylate copolymer, or a laminated structure with more than two layers thereof. In addition, a typical porous nonwoven fabric can be used, for example, a nonwoven fabric formed by high melting point glass fiber, polyethylene terephthalate fiber, etc. In addition, a coating separator comprising a ceramic component or a polymer material can be used to ensure heat resistance or mechanical strength, and can be selectively used in a single layer or multilayer structure.
[0115] In addition, the electrolyte used in the present invention may be an organic liquid electrolyte, an inorganic liquid electrolyte, a solid polymer electrolyte, a gel polymer electrolyte, a solid inorganic electrolyte, a molten inorganic electrolyte, etc. that can be used in the manufacture of a lithium secondary battery, but is not limited thereto.
[0116] Specifically, the electrolyte may include an organic solvent and a lithium salt.
[0117] Any organic solvent can be used without particular limitation, as long as it can act as a medium through which ions participating in the electrochemical reaction of the battery can move. Specifically, as the organic solvent, ester solvents such as methyl acetate, ethyl acetate, γ-butyrolactone and ε-caprolactone can be used; ether solvents such as dibutyl ether or tetrahydrofuran; ketone solvents such as cyclohexanone; aromatic hydrocarbon solvents such as benzene and fluorobenzene; carbonate solvents such as dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (MEC), ethyl methyl carbonate (EMC), ethylene carbonate (EC) and propylene carbonate (PC); alcohol solvents such as ethanol and isopropanol; nitrile such as R-CN (wherein R is a linear, branched or cyclic C2 to C20 hydrocarbon group and may contain a double bond aromatic ring or an ether bond); amides such as dimethylformamide; dioxolanes such as 1,3-dioxolanes; or cyclopentane sulfone. Among these solvents, carbonate solvents are preferred, and more preferably a mixture of a cyclic carbonate (e.g., ethylene carbonate or propylene carbonate) with high ionic conductivity and high dielectric constant and a linear carbonate compound (e.g., ethyl methyl carbonate, dimethyl carbonate or diethyl carbonate) with low viscosity, the mixture can increase the charge / discharge performance of the battery. In this case, when the cyclic carbonate and the linear carbonate are mixed in a volume ratio of about 1:1 to about 1:9, the performance of the electrolyte may be excellent.
[0118] Any compound can be used as the lithium salt without particular limitation, as long as it can provide the lithium ions used in the lithium secondary battery. Specifically, as the lithium salt, LiPF6, LiClO4, LiAsF6, LiBF4, LiSbF6, LiAlO4, LiAlCl4, LiCF3SO3, LiC4F9SO3, LiN(C2F5SO3)2, LiN(C2F5SO2)2, LiN(CF3SO2)2, LiCl, LiI, LiB(C2O4)2, etc. can be used. The lithium salt can be used in a concentration range of 0.1M to 2.0M. When the concentration of the lithium salt is within the above range, the electrolyte has suitable conductivity and viscosity, thereby showing excellent performance, and lithium ions can be effectively moved.
[0119] In the electrolyte, in order to improve the life properties of the battery, inhibit the reduction of the battery capacity, and improve the discharge capacity of the battery, one or more additives may be further included, for example, halogenated alkylene carbonate compounds such as difluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ethers, ethylenediamine, n-glyme, hexamethylphosphoric triamide, nitrobenzene derivatives, sulfur, quinone imine dyes, N-substituted Oxazolidinone, N,N-substituted imidazolidine, ethylene glycol dialkyl ether, ammonium salt, pyrrole, 2-methoxyethanol or aluminum chloride, etc. At this time, the content of the additive may be 0.1 to 5 parts by weight based on 100 parts by weight of the total weight of the electrolyte.
[0120] The above-mentioned lithium secondary battery containing the positive electrode material according to the present invention stably exhibits excellent discharge capacity, output properties and life properties, and therefore, can be used in portable devices such as mobile phones, notebook computers and digital cameras, and electric vehicles such as hybrid electric vehicles (HEV) fields.
[0121] Therefore, according to another embodiment of the present invention, a battery module including the lithium secondary battery as a unit cell, and a battery pack including the battery module are provided.
[0122] The battery module or the battery pack can be used as a power source for one or more medium-to-large devices, such as power tools, electric vehicles such as electric vehicles (EV), hybrid electric vehicles (HEV), and plug-in hybrid electric vehicles (PHEV), or power storage systems.
[0123] The external shape of the lithium secondary battery of the present invention is not particularly limited, but may be a can-shaped cylindrical shape, a square shape, a pouch shape, a coin shape, or the like.
[0124] The lithium secondary battery according to the present invention can be used as a battery cell used as a power source for small devices, and can also be preferably used as a unit cell of a medium or large battery module including a plurality of battery cells.
[0125] Mode for Carrying Out the Invention
[0126] Hereinafter, the present invention will be described in detail with reference to the embodiments. However, the embodiments according to the present invention may be modified into other various forms, and the scope of the present invention should not be interpreted as being limited to the embodiments described below. The embodiments of the present invention are provided to more fully describe the present invention to those skilled in the art.
[0127] Example 1
[0128] A mixture of lithium (containing LiNiO2 and 1.5M Li) and benzophenone was mixed with tetrahydrofuran (THF) and then reacted in an inert atmosphere for one day. Next, the resulting mixture was filtered and dried. Afterwards, the filtered and dried mixture was washed with THF and then dried in a vacuum to obtain a powder in which trigonal Li2NiO2 and LiNiO2 were mixed. Next, the powder was dried at 225°C for 14 hours and then heat-treated in a helium atmosphere to obtain a Li2NiO2 powder with a trigonal structure having improved crystallinity.
[0129] Next, Fe2O3 and LiOH·H2O were mixed in a weight ratio of 1:1 and then fired at 850°C for 20 hours in a nitrogen atmosphere to obtain Li5FeO4 with an orthorhombic structure.
[0130] The Li2NiO2 and Li5FeO4 obtained above were dry-mixed in a ratio of 10:1, and then heat-treated at 300°C for 4 hours for coating, so that Li5FeO4 was 2 parts by weight based on 100 parts by weight of Li2NiO2 on the surface of Li2NiO2, thereby preparing an irreversible additive.
[0131] Comparative Example 1
[0132] Commercially available Li2NiO2 powder (POSCO, LNO_DN20) having an orthorhombic structure was prepared as an irreversible additive.
[0133] Comparative Example 2
[0134] Li2NiO2 powder having a trigonal structure was prepared in the same manner as in Example 1, except that Li5FeO4 was not coated and was prepared as an irreversible additive.
[0135] Experimental Example 1: X-ray diffraction (XRD) pattern measurement
[0136] The Li2NiO2 powder and Li5FeO4 powder prepared in Example 1 were measured by XRD using Cu-Kα radiation. The analysis results are as follows: Figure 3 and Figure 4 shown.
[0137] In addition, the Li2NiO2 powder of Comparative Example 1 was subjected to XRD measurement using Cu-Kα radiation, and the analysis results are as follows: Figure 5 shown.
[0138] pass Figure 3 and Figure 4The XRD patterns shown confirm that the Li2NiO2 powder prepared in Example 1 has a peak corresponding to a trigonal structure, while the Li5FeO4 powder prepared in Example 1 has a peak corresponding to an orthorhombic structure.
[0139] In addition, through Figure 5 , it can be confirmed that the Li2NiO2 powder of Comparative Example 1 has a peak corresponding to the orthorhombic structure.
[0140] Experimental Example 2: Measurement of oxygen formation energy
[0141] The oxygen formation energy of each irreversible additive of Example 1 and Comparative Examples 1 and 2 was confirmed. Specifically, the oxygen formation energy according to the change of the crystal structure was calculated by applying the density functional theory (DFT) calculation method using the Vienna Ab-initio Simulation package (VASP) program, and the calculation results are shown in the following Table 1. At this time, the oxygen formation energy was calculated based on the density functional theory (DFT) and the PBE functional PAW_PBE pseudopotential under the following conditions.
[0142] Cut-off energy: 520 eV, calculation model: with Li 40 Fe8O 32 Atomic supercell, oxygen vacancy (V0) generation concentration = 1 / 32 (~3.13 atomic %), calculated value based on O2 gas (O-rich environment).
[0143] [Table 1]
[0144]
[0145] Oxygen formation energy is a calculated value of the energy required to remove one oxygen, and it can be determined that the higher the oxygen formation energy, the more stable the structure. As shown in Table 1 above, compared with the irreversible additive made of orthorhombic lithium nickel oxide in Comparative Example 1 and the irreversible additive made of trigonal lithium nickel oxide without coating in Comparative Example 2, the irreversible additive prepared by coating trigonal lithium nickel oxide with Li5FeO4 in Example 1 has a higher oxygen formation energy, indicating that the irreversible additive in Example 1 has a more excellent structural stability than the irreversible additives in Comparative Examples 1 and 2.
Claims
1. A positive electrode material comprising an irreversible additive and a positive electrode active material, The irreversible additive comprises: A lithium nickel oxide having a trigonal crystal structure and represented by the following formula 1; and A coating located on the surface of the lithium nickel oxide represented by formula 1 and containing a compound represented by the following formula 2: [Formula 1] Li 2+a Ni 1-b M1 b O 2+c , Wherein in the above formula 1, 0≤a≤0.2, 0≤b≤0.5 and 0≤c≤0.2, and M1 is one or more selected from the group consisting of Cu, Mg, Pt, Al, Co, P and B, [Formula 2] Li 5+c FeO 4-d A d , Wherein in the above formula 2, 0≤c≤0.2 and 0≤d≤0.5, and A is one or more selected from the group consisting of F, Cl, Br, I, At and S.
2. The positive electrode material according to claim 1, wherein the space group of the lithium nickel oxide represented by the above formula 1 belongs to P3-m1.
3. The positive electrode material according to claim 1, wherein the lithium nickel oxide represented by the above formula 1 contains lithium and nickel in a molar ratio of 1.5:1 to 2:
1.
4. The positive electrode material according to claim 1, wherein the lithium nickel oxide represented by the above formula 1 is Li2NiO2.
5. The positive electrode material according to claim 1, wherein the compound represented by formula 2 has an orthorhombic crystal structure.
6. The positive electrode material according to claim 1, wherein the compound represented by the above formula 2 is Li5FeO4.
7. The positive electrode material according to claim 1, wherein based on 100 parts by weight of the total weight of the lithium nickel oxide represented by the above formula 1, the content of the compound represented by the above formula 2 is 1 to 10 parts by weight.
8. The positive electrode material according to claim 1, wherein the positive electrode active material is represented by the following [Formula 3]: [Formula 3] Li 1+f Ni x Co y M3 z M4 w O2, Wherein in the above formula 3, 0≤f≤0.2, 0<x<1, 0<y<1, 0<z<1 and 0≤w≤0.1, M3 is one or more of Mn and Al, and M4 is selected from the group consisting of Al, Mg, Ti, W, Zr, V, Fe, Y and Mo One or more.
9. The positive electrode material according to claim 1, wherein the positive electrode active material is represented by the following [Formula 4]: [Formula 4] Li 1+f1 Ni x1 Co y1 Mn z1 Al z2 M4 w1 O2, Wherein in the above formula 4, 0≤f1≤0.2, 0.8≤x1<1, 0<y1<0.2, 0<z1<0.2, 0<z2<0.2, and 0≤w1≤0.1, and M4 is selected from the group consisting of Mg, Ti, W, Zr, V, Fe, Y and Mo One or more.
10. The positive electrode material according to claim 1, wherein based on 100 parts by weight of the positive electrode active material, the content of the irreversible additive is 5 to 20 parts by weight.
11. A lithium secondary battery comprising: A positive electrode comprising the positive electrode material according to claim 1; A negative electrode positioned facing the positive electrode; A separator interposed between the positive electrode and the negative electrode; and An electrolyte.
12. The lithium secondary battery according to claim 11, wherein the negative electrode comprises a silicon-based negative electrode active material.
Citation Information
Patent Citations
Method for regulating terminal voltage of cathode during overdischarge and cathode active material for lithium secondary battery
CN1745490A